Strategi Efektif dalam Meningkatkan Kemampuan Literasi Membaca pada anak Sekolah Dasar - Al Firah; Ananda Hadi Elyas (Unity Academy, 2024)
In order to enhance reading literacy among elementary school children in orphanages, this Community Service Program (PKM) is designed to implement and evaluate various interactive learning strategies. The program aims to identify the most effective approaches to improving reading skills while also increasing the motivation and confidence of the children in reading. This PKM involves 50 children from two different orphanages, where each implements different strategies, including joint reading sessions, group discussions, and the use of varied and engaging reading materials. The methodology used includes both qualitative and quantitative evaluations. Quantitative data were obtained through pre-tests and post-tests to measure improvements in reading literacy scores, while qualitative data were collected through interviews with caregivers and feedback from the children. The results show a significant improvement in the children's reading literacy scores, from an average of 60 at the start of the program to 82 after its implementation. Additionally, positive feedback was received from both children and caregivers, indicating an increase in interest and confidence in reading. Several challenges were identified during implementation, including the need for greater access to a variety of reading materials and the need for sustainability strategies for the program. This Community Service Program provides evidence that interactive and supportive learning strategies can significantly improve the reading literacy abilities of children in orphanages. The implications of this study are important for the development of educational programs aimed at enhancing literacy in underprivileged environments.